Septic abortion in adolescents - Chumbe, Ovidio (2015)
OBJECTIVE: To determine incidence, evolution, characteristics, and complications of septic abortion in adolescents. DESIGN: Epidemiological study from 1990 through 1996. RESULTS: From 1709 abortions, 285 occurred in adolescents. General abortion rate was 274,5 per 1 000 lnb, in non-adolescents 290 and in adolescents 203. Incidence ofseptic abortion was 16,7%, distributed in 16,1% in patients over 19 years and 20,5% in adolescents (p < 0,05), especially at ages 18 and 19; 42% had pregnancy interruption above 12 weeks gestation: 27% had a previous pregnancy. Most frequent complications at hospitalization were anemia and septic shock; hysterectomy wasperformed in 8,5%. CONCLUSION: Sept abortion is tbefirst cause of maternal mortality at our Hospital, butfortunately is less frequent in adolescents.